2010
DOI: 10.1016/j.ijge.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age-related Changes in Tactile Sensibility and Muscular Strength on Hand Function in Older Adult Females

Abstract: s u m m a r yBackground: Aging affects the human hand function. For example, a decline in manual dexterity often accompanies old age. This decline corresponds to age-related changes in muscle and/or tactile functions. This study investigated whether age-related changes in muscular strength and tactile sensibility are related to the hand function. Methods: The subjects consisted of 64 older adult females. The hand function was assessed using Perdue pegboard test. The handgrip strength was measured using a handg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Reduced cutaneous sensation has also been correlated with poor hand function (Dellon et al 1997;Melchior et al 2007), but the relationship between higher cutaneous thresholds at the fingertips and impaired motor performances are inconsistent (Cole et al 1998;Ranganathan et al 2001;Aoki and Fukuoka 2010;Murata et al 2010). It has also been suggested that work-related expertise in fine dexterous manipulation does not attenuate age-related changes in cutaneous sensation at the fingertip (Reuter et al 2012).…”
Section: Functional Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced cutaneous sensation has also been correlated with poor hand function (Dellon et al 1997;Melchior et al 2007), but the relationship between higher cutaneous thresholds at the fingertips and impaired motor performances are inconsistent (Cole et al 1998;Ranganathan et al 2001;Aoki and Fukuoka 2010;Murata et al 2010). It has also been suggested that work-related expertise in fine dexterous manipulation does not attenuate age-related changes in cutaneous sensation at the fingertip (Reuter et al 2012).…”
Section: Functional Implicationsmentioning
confidence: 99%
“…Age-related changes in sensation are usually investigated at a single site, typically the index fingertip (e.g., Thornbury and Mistretta 1981;Desrosiers et al 1996;Tremblay et al 2005;Murata et al 2010), although the tip of the little finger (Bruce 1980), two to three fingertips (Cole et al 1998;BearLehman et al 2003), or all five fingertips (Kalisch et al 2008;Aoki and Fukuoka 2010), have been compared. Changes in cutaneous sensation are more frequently reported using two-point discrimination, again most often at the fingertips (e.g., Bovenzi and Zadini 1989;Woodward 1993;Desrosiers et al 1996;Stevens and Choo 1996;Kalisch et al 2008;van Nes et al 2008) although the palm and dorsal surface have been studied (Axelrod and Cohen 1961;Gellis and Pool 1977;Stevens and Choo 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This was in line with hypotheses and past research (Hoyer et al, 2004 ; Gilmore et al, 2006 ) especially with regard to the SS and Cod which are WAIS clinical measures of processing speed, that are also heavily reliant on motor speed (Ebaid et al, 2017b ). In line with this, manual motor speed has been consistently reported to slow with increased age (Murata et al, 2010 ; Ebaid et al, 2017b ). Elevated depression and anxiety symptoms are also often reported to impede cognitive performance in older populations (Beaudreau and O’Hara, 2008 , 2009 ), however, it is interesting to note that our healthy older sample reported lower depression anxiety and stress scores than our younger adults, making negative affective issues unlikely to have impeded task performance in this case.…”
Section: Discussionmentioning
confidence: 64%
“…At the age of 20 to 35 years old, the muscle strength increases and after 35 years old it will decreases (Lynch et al 1999). According to Murata et al (2010), as the human grow older, function of their hand will be decreased and this happened due to the changes of hand muscle. However, there was another study which stated that the handgrip strength can also be influenced by the position of the elbow and the size of hand (Espana-Romero et al 2010;Murugan et al 2013).…”
Section: Discussionmentioning
confidence: 99%